Metrology and sustainability: Using sustainability audits in New Zealand to elaborate the complex politics of measuring. (May 2017) - Rosin, Christopher; Campbell, Hugh; Reid, John
Abstract: The study of metrology has emerged in the last couple of years as a useful new approach to understanding economic practices and networks. In this paper, we draw on research experience with the New Zealand kiwifruit and wine sectors as well as the development of an indigenous branding project to examine the role of metrics in promoting sustainable practice. We first identify two more commonly theorised aspects in which metrics operate: as measures (i.e., simple representations of uncontested values, and as tools (i.e., signifiers of the power of wider institutions or structures. We also argue, however, that metrics have operated in a third, potentially more controversial, manner in exerting their own power as 'material agents' within economic networks. In each case, there are elements of the development of new economic practices that suggest that metrics can work as material agents in re-organising economic activity and reordering social networks